Enhancing tristetraprolin activity reduces the severity of cigarette smoke‐induced experimental chronic obstructive pulmonary disease. Issue 10 (28th October 2019) - Nair, Prema M; Starkey, Malcolm R; Haw, Tatt Jhong; Liu, Gang; Collison, Adam M; Mattes, Joerg; Wark, Peter A.; Morris, Jonathan C; Verrills, Nikki M; Clark, Andrew R; Ammit, Alaina J; Hansbro, Philip M
Abstract: Objective: Chronic obstructive pulmonary disease (COPD) is a progressive disease that causes significant mortality and morbidity worldwide and is primarily caused by the inhalation of cigarette smoke (CS). Lack of effective treatments for COPD means there is an urgent need to identify new therapeutic strategies for the underlying mechanisms of pathogenesis. Tristetraprolin (TTP) encoded by the Zfp36 gene is an anti‐inflammatory protein that induces mRNA decay, especially of transcripts encoding inflammatory cytokines, including those implicated in COPD. Methods: Here, we identify a novel protective role for TTP in CS‐induced experimental COPD using Zfp36 aa/aa mice, a genetically modified mouse strain in which endogenous TTP cannot be phosphorylated, rendering it constitutively active as an mRNA‐destabilising factor. TTP wild‐type ( Zfp36 +/+ ) and Zfp36 aa/aa active C57BL/6J mice were exposed to CS for four days or eight weeks, and the impact on acute inflammatory responses or chronic features of COPD, respectively, was assessed. Results: After four days of CS exposure, Zfp36 aa/aa mice had reduced numbers of airway neutrophils and lymphocytes and mRNA expression levels of cytokines compared to wild‐type controls. After eight weeks, Zfp36 aa/aa mice had reduced pulmonary inflammation, airway remodelling and emphysema‐like alveolar enlargement, and lung function was improved. We then used pharmacological treatments in vivo (protein phosphatase 2A activator, AAL(S), and the proteasome inhibitor, bortezomib) to promote the activation and stabilisation of TTP and show that hallmark features of CS‐induced experimental COPD were ameliorated. Conclusion: Collectively, our study provides the first evidence for the therapeutic potential of inducing TTP as a treatment for COPD. Abstract : Cigarette smoke (CS) exposure increases the mRNA expression of inflammatory mediators resulting in pulmonary inflammation. Ongoing inflammation drives the development of airway remodelling and emphysema, subsequently leading to lung function decline. This study highlights the importance of having active TTP to control CS‐induced inflammation, pulmonary remodelling, emphysema and impaired lung function in mice.